Prior Anti-Angiogenic TKI-Based Treatment as Potential Predisposing Factor to Nivolumab-Mediated Recurrent Thyroid Disorder Adverse Events in mRCC Patients: A Case Series - Luigi Liguori; Angelo Luciano; Giovanna Polcaro; Alessandro Ottaiano; Marco Cascella; Francesco Perri; Stefano Pepe; Francesco Sabbatino (Biomedicines, 2023)
Immune checkpoint inhibitors (ICIs) targeting programmed cell death 1 (PD-1) or its ligand 1 (PD-L1) have revolutionized the management of many types of solid tumors, including metastatic renal cell carcinoma (mRCC). Both sequential and combinatorial therapeutic strategies utilizing anti-PD-1 monoclonal antibodies (mAbs) and anti-angiogenic tyrosine kinase inhibitors (TKIs) have demonstrated to improve the survival of patients with mRCC as compared to standard therapies. On the other hand, both ICIs and TKIs are well known to potentially cause thyroid disorder adverse events (TDAEs). However, in the context of sequential therapeutic strategy, it is not clear whether prior anti-angiogenic TKI may increase the risk and/or the severity of ICI-related TDAEs. In this work, by describing and analyzing a case series of mRCC patients treated sequentially with prior TKIs and then with ICIs, we investigated the role of prior anti-angiogenic TKI-based treatment as a potential predisposing factor to anti-PD-1-mediated recurrent TDAEs, as well as its potential impact on the clinical characteristics of nivolumab-mediated recurrent TDAEs. Fifty mRCC patients were included in the analysis. TKI-mediated TDAEs were reported in ten out of fifty patients. TKI-mediated TDAEs were characterized by hypothyroidism in all ten patients. Specifically, 40%, 40% and 20% of patients presented grade 1, 2 and 3 hypothyroidisms, respectively. Following tumor progression and during anti-PD-1 nivolumab treatment, five out of ten patients developed anti-PD-1 nivolumab-mediated recurrent TDAEs. Anti-PD-1 nivolumab-mediated recurrent TDAEs were characterized by an early transient phase of thyrotoxicosis and a late phase of hypothyroidism in all five patients. The TDAEs were grade 1 and 2 in four and one patients, respectively. Prior anti-angiogenic TKI did not modify the clinical characteristics of nivolumab-mediated recurrent TDAEs. However, all five patients required an increased dosage of levothyroxine replacement therapy. In conclusion, our work suggests that prior anti-angiogenic TKI-based treatment significantly increases the risk of ICI-mediated recurrent TDAEs in patients with mRCC without modifying their clinical characteristics. The most relevant effect for these patients is the need to increase the dosage of lifelong levothyroxine replacement therapy.